2010
DOI: 10.1007/s00401-010-0764-0
|View full text |Cite
|
Sign up to set email alerts
|

Distinct pathological subtypes of FTLD-FUS

Abstract: Most cases of frontotemporal lobar degeneration (FTLD) are characterized by abnormal intracellular accumulation of either tau or TDP-43 protein. However, in ~10% of cases, composed of a heterogenous collection of uncommon disorders, the molecular basis remains to be uncertain. We recently discovered that the pathological changes in several tau/TDP-43-negative FTLD subtypes are immunoreactive (ir) for the fused in sarcoma (FUS) protein. In this study, we directly compared the pattern of FUS-ir pathology in case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
150
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(174 citation statements)
references
References 58 publications
11
150
4
Order By: Relevance
“…The main pathological features in FALS with FUS mutations are FUS-positive protein aggregates in neuronal cytoplasm and dendrites (1,2). While the majority of these aggregates are identified in the spinal motor neurons, FUS-positive aggregates have also been found in neurons in cerebral cortex and brainstem nuclei (3,4), raising the possibility that FUS mutations may have a broader impact on the functions of other neuronal subtypes. Consistent with these observations, a subset of FALS-FUS patients also exhibits cognitive impairments during the developmental or degenerative processes.…”
Section: Introductionmentioning
confidence: 99%
“…The main pathological features in FALS with FUS mutations are FUS-positive protein aggregates in neuronal cytoplasm and dendrites (1,2). While the majority of these aggregates are identified in the spinal motor neurons, FUS-positive aggregates have also been found in neurons in cerebral cortex and brainstem nuclei (3,4), raising the possibility that FUS mutations may have a broader impact on the functions of other neuronal subtypes. Consistent with these observations, a subset of FALS-FUS patients also exhibits cognitive impairments during the developmental or degenerative processes.…”
Section: Introductionmentioning
confidence: 99%
“…However, relevant to this review, glial pathology is observed in all cases of familial and sporadic ALS (Neumann et al 2007;Nishihira et al 2008;Zhang et al 2008;Seilhean et al 2009;Hewitt et al 2010;Yamamoto-Watanabe et al 2010;Mackenzie et al 2011;Robertson et al 2011). Genes known to be linked to familial ALS are ubiquitously expressed, and ubiquitinated aggregates of ALScausing mutant proteins (such as SOD1 or TDP-43) are found in both neurons and glial cells (Bruijn et al 1997;Pasinelli et al 2000;Stieber et al 2000;Nishihira et al 2008;Zhang et al 2008;Forsberg et al 2011).…”
Section: Astrocytes In Alsmentioning
confidence: 99%
“…Recent studies, however have clearly demonstrated the involvement of both the white matter and subcortical areas in this disorder. For example, in FTLD-FUS and FTLD caused by C9orf mutation there is marked involvement of the caudate and thalamic nuclei, respectively [30]. …”
Section: Discussionmentioning
confidence: 99%